Economic accounts for agriculture and farm income in Senegal - Fofana, Ismaël; Tankari, Mahamadou Roufahi; Traoré, Fousseini (International Food Policy Research Institute, 2017)
A monitoring and evaluation (M&E) system is of critical importance for evidence- and outcome-based planning and implementation in agriculture. The availability of and access to timely and reliable data to inform the M&E system is an undeniable asset. Our analysis highlights the use of survey data to generate relevant information and knowledge on the agricultural sector. The Poverty Monitoring Survey carried out in Senegal in 2011 is used to build the economic accounts for agriculture, which identify a value added of 581 billion CFA francs generated by Senegal’s farm households, representing 60 percent of the sector’s value added in 2011. The average farm household generated 646,500 CFA francs from farming in that same year. The information from the economic accounts for agriculture offers valuable inputs for decision-support tools such as the geographical information platforms (e-atlas) and social accounting matrixes used in strategic analyses and agricultural policy planning.